Fabrication and mechanical characterization of binderless boards from sugarcane bagasse fibers - Hasanuddin, Iskandar; Faurantia, Faurantia; Mawardi, Indra (Politeknik Negeri Lhokseumawe, 2025)
Agricultural waste management is a pressing environmental concern, as traditional disposal methods like incineration contribute to pollution. This study explores the fabrication and evaluation of binderless boards made from sugarcane bagasse fibers, eliminating the need for synthetic binders. Bagasse fibers were processed at mesh sizes of 20 and 40, then hot-pressed at 190°C under 9.6 MPa pressure for 15 and 25 minutes, achieving a targeted thickness of 10 mm. The physical and mechanical properties, including density, water absorption, thickness swelling, Modulus of Rupture (MOR), and Modulus of Elasticity (MOE), were analyzed. Results showed that particle size and pressing time significantly influenced board properties. The highest performance was observed in the E25 sample (40-mesh, 25-minute pressing), with a density of 0.52 g/cm³, MOR of 2.69 MPa, MOE of 293.82 MPa, water absorption of 134.66%, and thickness swelling of 16.80%. These findings suggest that optimizing particle size and pressing conditions enhances binderless board strength and dimensional stability, making sugarcane bagasse a viable raw material for sustainable panel production.